Pseudophichthys splendens Lea 1913 - Melo, Marcelo R. S.; Nunan, Gustavo W. A.; Braga, Adriana C.; Costa, Paulo A. S. (Zenodo, 2009)
Pseudophichthys splendens (Lea, 1913) (Fig. 2 H) Material examined. One specimen, 277.0 mm TL: MNRJ 26828 (1, 277.0 mm), T, E-498. Distribution. Pseudophichthys splendens was described from the eastern North Atlantic, and is widespread in the tropical Atlantic. In the eastern Atlantic, it is known from the Azores to the Gulf of Guinea (Smith 1990); in the western Atlantic it is known from the east coast of Florida, USA, throughout the Gulf of Mexico, Caribbean, and Guyana to about 30º S off the Atlantic coast of South America (Uyeno et al. 1983; Smith 1989b; Smith 2002). Published as part of Melo, Marcelo R. S., Nunan, Gustavo W. A., Braga, Adriana C. & Costa, Paulo A. S., 2009, The deep-sea Anguilliformes and Saccopharyngiformes (Teleostei: Elopomorpha) collected on the Brazilian continental slope, between 11 and 23 S, pp. 1-20 in Zootaxa 2234 on page 8, DOI: 10.5281/zenodo.190386